Interspeech 2020 2020
DOI: 10.21437/interspeech.2020-2768
|View full text |Cite
|
Sign up to set email alerts
|

Coswara — A Database of Breathing, Cough, and Voice Sounds for COVID-19 Diagnosis

Abstract: The COVID-19 pandemic presents global challenges transcending boundaries of country, race, religion, and economy. The current gold standard method for COVID-19 detection is the reverse transcription polymerase chain reaction (RT-PCR) testing. However, this method is expensive, time-consuming, and violates social distancing. Also, as the pandemic is expected to stay for a while, there is a need for an alternate diagnosis tool which overcomes these limitations, and is deployable at a large scale. The prominent s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
219
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(220 citation statements)
references
References 17 publications
(17 reference statements)
1
219
0
Order By: Relevance
“…The BI-AT-GRU model involves the bidirectional bids and attention of the GRU neural network, and it can differentiate between six forms of clinical respiratory types, such as Eupnea, Tachypnea, Bradypnea, Biots, Cheyne-Stokes, and Central-Apnea. Sharma et al [57] intended to create the laboratory diagnostic techniques of COVID-19 for sputum testing. In roder to test biomarkers in acoustics, the project, called Coswara, used cough, breath, and speech sounds.…”
Section: Observing Covid-19 Through Ai-based Cough Sound Analysismentioning
confidence: 99%
“…The BI-AT-GRU model involves the bidirectional bids and attention of the GRU neural network, and it can differentiate between six forms of clinical respiratory types, such as Eupnea, Tachypnea, Bradypnea, Biots, Cheyne-Stokes, and Central-Apnea. Sharma et al [57] intended to create the laboratory diagnostic techniques of COVID-19 for sputum testing. In roder to test biomarkers in acoustics, the project, called Coswara, used cough, breath, and speech sounds.…”
Section: Observing Covid-19 Through Ai-based Cough Sound Analysismentioning
confidence: 99%
“…Throughout the COVID-19 pandemic there have been numerous efforts to compile data sets of breath and cough audio recordings, including ‘Coughvid’, 3 ‘Breathe for Science’ ( https://www.breatheforscience.com ), ‘Coswara’ 4 and ‘CoughAgainstCovid’. 5 With their release, several studies have been published that leverage audio signals alongside machine learning to detect the virus.…”
Section: Related Workmentioning
confidence: 99%
“…They have concluded that it is possible to distinguish COVID-19 cough sounds from healthy cough using a simple binary machine learning classifier. This points to the potential of using cough sounds to diagnose COVID-19 (35)(36)(37). The cough sound can also be used to detect other respiratory illnesses.…”
Section: Related Workmentioning
confidence: 97%